Maximum values of total differentials and linear hulls of block symmetric ciphers - Лисицкий, Константин Евгеньевич (Technology audit and production reserves, 2014)
The approach to obtaining the estimates of provable block symmetric ciphers security against differential and linear cryptanalysis attacks, represented by the maximum values of differential and linear probabilities of multi-cycle enciphering transformations is proposed in the paper. The main objective of the research is to obtain the design ratios to calculate these indicators. As it is known, today these indicators are represented as estimated values, significantly differing from true that was determined using the new methodology for estimating the indicators of provable block symmetric ciphers security against differential and linear cryptanalysis attacks, developed recently. The basic mathematical apparatus of the random permutation theory is described, and the calculation results of provable security indicators, obtained using this mathematical apparatus for ciphers with 128-bit input, and in particular for the cipher Rijndael and ciphers, presented at the recent Ukrainian competition are given in the paper. The obtained results allow to obtain more objective data on ciphers security indicators, which can be used for improving the quality of expert solutions and conclusions on the improvement degree of the projects, submitted to the contest, as well as for selecting new promising solutions and developments on building ciphers. It is concluded that all these ciphers have the same parameters both for the differential and linear properties, almost equal to 2-121.